(untitled) (Applied Biological Research, 2025)
Heat shock proteins (HSPs) play a crucial protective role during heat stress in dairy animals by acting as molecular chaperones that facilitate the folding, unfolding, and refolding of denatured proteins. The present study aimed to molecularly characterize the HSPB6 gene and to assess the association between identified single nucleotide polymorphisms (SNPs) and physiological parameters in buffaloes. A total of ninety-six female buffaloes reared at the Directorate Livestock Farms (DLF), GADVASU were included in the study. The HSPB6 gene, located on the 18th autosome of Bubalus bubalis (BTA 18), plays an important role in apoptosis and stress response. Gene-specific forward and reverse primers were designed to amplify fragments of 578 bp and 720 bp, respectively. Two polymorphic loci were identified in the HSPB6 gene when compared with the reference sequence (NCBI GenBank accession AC059174.1), including a translational mutation at locus A1277G in exon 2 and a transversion mutation at locus A1123C in the intron. The nucleotide substitution g.1277A>G in exon 2 was non-synonymous, resulting in an amino acid change at position 91 from lysine (K) to glutamic acid (E). The SNP at locus g.1123A>C was found to be significantly associated (p < 0.01) with respiration rate. Furthermore, buffaloes with the AG genotype at locus g.1277A>G exhibited the lowest values of respiration rate, rectal temperature, and heat tolerance coefficient, indicating greater thermotolerance. However, further experimental studies involving larger populations are required to validate the relationship between allelic variations in key heat shock protein genes and heat stress tolerance.